Keamanan bahan pangan di era teknologi: mengelola risiko bahan kimia dalam produk makanan - Andriani, Nadia Rizki (Maliki Interdisciplinary Journal, 2026)
Chemicals are substances or compounds with specific compositions and properties that are widely used in everyday life, including in the food industry. In food products, chemicals occur both naturally, such as carbohydrates, proteins, vitamins, and bioactive compounds, and as food additives. Additives such as preservatives (sodium benzoate), colorings (tartrazine), sweeteners (aspartame), and flavor enhancers (MSG) serve to improve quality and flavor, and extend shelf life. However, their use raises concerns regarding food safety, as excessive consumption can have negative health effects. This examines the benefits and risks of using chemicals in food based on a review of scientific literature. The study shows that although chemicals play a crucial role in supporting food security, monitoring their dosage and regulating their use is essential to minimize adverse impacts. Therefore, consumer awareness and strict regulatory enforcement are key to balancing industry needs with public health protection.